2021
DOI: 10.1007/s00424-021-02576-5
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic GABAB receptor–mediated network excitation in the medial prefrontal cortex of Tsc2+/- mice

Abstract: The TSC1 and TSC2 tumor suppressor genes control the activity of mechanistic target of rapamycin (mTOR) pathway. Elevated activity of this pathway in Tsc2+/- mouse model leads to reduction of postsynaptic GABAB receptor–mediated inhibition and hyperexcitability in the medial prefrontal cortex (mPFC). In this study, we asked whether presynaptic GABAB receptors (GABABRs) can compensate this shift of hyperexcitability. Experiments were performed in brain slices from adolescent wild-type (WT) and Tsc2+/- mice. Min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The alteration in the balance between inhibitory and excitatory synaptic transmission is emerging as a fundamental principle underlying a variety of neuropsychiatric and neurodevelopmental disorders, such as ASD and epilepsy. Using the ratio of mEPSCs over mIPSCs to describe the change of E/I balance is a common method ( Bassetti et al, 2021 ; Huang et al, 2021 ). It can show the whole view of the excitatory synaptic inputs and inhibitory synaptic inputs from the postsynaptic neuron.…”
Section: Discussionmentioning
confidence: 99%
“…The alteration in the balance between inhibitory and excitatory synaptic transmission is emerging as a fundamental principle underlying a variety of neuropsychiatric and neurodevelopmental disorders, such as ASD and epilepsy. Using the ratio of mEPSCs over mIPSCs to describe the change of E/I balance is a common method ( Bassetti et al, 2021 ; Huang et al, 2021 ). It can show the whole view of the excitatory synaptic inputs and inhibitory synaptic inputs from the postsynaptic neuron.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding EPSCs, we observed that while there was a non-significant trend towards increased EPSC frequency during NA wash in for both groups (Figure 4G), no statistically significant differences could be found between the two EGFP-shRNA-expressing groups (Figure 4G-H). Based on these results, we plotted the ratio of EPSC over IPSC frequencies during baseline, NA wash in and NA wash out (Figure 5A) to estimate an E/I ratio (Zhou et al, 2009;Bassetti et al, 2021;Kirischuk, 2022). This plot highlights that in the Adra1a-shRNA group, there is an imbalance in favor of excitation, when the circuit is either in its basal state, or following the wash out of NA from the recording bath.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the E/I ratio, the results were similar, but by different implementation: male rats by more excited glutamatergic neurons, female rats by less excited GABAergic neurons. In the future, the exact E/I ratio can be examined by ratio of (m/s) EPSC frequency to (m/s) IPSC frequency 22 …”
Section: Discussionmentioning
confidence: 99%
“…In the future, the exact E/I ratio can be examined by ratio of (m/s) EPSC frequency to (m/s) IPSC frequency. 22 Sex differences in the nervous system due to estrous cycle, sex hormones, and their receptors have gained increasing attention in recent years. 23 Yousuf et al demonstrated that infralimbic estradiol could enhance neuronal excitability of female rats, 24 which could be a putative reason for the sexually dimorphic effects.…”
Section: Different Alterations In Excitability Of Mpfc Gabaergic Neuronsmentioning
confidence: 99%